KADAR LOGAM BERAT Pb (TIMBAL) SUSU KAMBING YANG DIBERI PAKAN SILASE LIMBAH SAYURAN - Aaf Falahudin; U.I.L. Rahmah (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2017)
The aim of this research is to get information of heavy metal content of Pb in goat milk fed with vegetables waste silage which is safe to be consumed by society. The experiments were carried out by using 16 pregnant 2 - 2,5 years old goat who were treated until the mother was lactated. The experimental design used was Completely Randomized Design with 4 treatments and 4 replications. The treatments applied were as follows: T0 = 100% forage (mixture of grass and legume), T1 = 80% forage + 20% vegetables waste silage, T2 = 60% forage + 40% silage vegetables waste, and T3 = 40% forage + 60% waste silage vegetables. The experiment was conducted for 5 months. The research results show that the feed silage vegetables waste very real produce milk production daily higher than the control of grass. The provision of silage vegetables waste very real produce metal Pb levels higher than control and be above threshold SNI 3141.1: 2011. So that it can be concluded that the silage vegetables waste not advisable done by farmers due to metal Pb in goat milk is still not safe to be consumed. Keywords : Silage, Vegetables Waste, Pb, Goat Milk.